2020
DOI: 10.3390/cancers12071982
|View full text |Cite
|
Sign up to set email alerts
|

The Biological Role of Sponge Circular RNAs in Gastric Cancer: Main Players or Coadjuvants?

Abstract: Circular RNAs (circRNAs) are a new class of long noncoding RNAs able to perform multiple functions, including sponging microRNAs (miRNAs) and RNA-Binding Proteins (RBPs). They play an important role in gastric carcinogenesis, but its involvement during gastric cancer (GC) development and progression are not well understood. We gathered miRNA and/or RBPs sponge circRNAs present in GC, and accessed their biological roles through functional enrichment of their target genes or ligand RBPs. We identified 54 sponge … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 105 publications
(197 reference statements)
0
10
0
Order By: Relevance
“…Gene functional enrichment conducted by Pereira et al . indicated that circRNA/miRNA/mRNA axes have the potency to directly affect pathways that are well-known to be dysregulated in the event of gastric carcinogenesis [ 22 ]. Our results demonstrated that circ0005654 was mainly concentrated in the cytoplasm, and dual-luciferase reporter assay was performed to confirm that circ0005654 could competitively share miR-363 with sp1 mRNA, serving as a sponge.…”
Section: Discussionmentioning
confidence: 99%
“…Gene functional enrichment conducted by Pereira et al . indicated that circRNA/miRNA/mRNA axes have the potency to directly affect pathways that are well-known to be dysregulated in the event of gastric carcinogenesis [ 22 ]. Our results demonstrated that circ0005654 was mainly concentrated in the cytoplasm, and dual-luciferase reporter assay was performed to confirm that circ0005654 could competitively share miR-363 with sp1 mRNA, serving as a sponge.…”
Section: Discussionmentioning
confidence: 99%
“…It is well known that circRNAs perform multiple functions via sponging miRNAs and RNA-binding proteins [ 26 ]. Our study found that miR-195-5p could directly bind with circ-FURIN, and BCL2, suggesting that circ-FURIN or BCL2 have targeted relationship with miR-195-5p.…”
Section: Discussionmentioning
confidence: 99%
“…Hif-2α is upregulated in hypoxic drug-resistant GC (HRGC) cells under a long-term hypoxic microenvironment and promotes GC metastasis through the miR-653-5p/miR-338-3P-NRP1 axis ( Jin et al, 2020b ). These circRNAs, which form complex RBP-circRNA-miRNA-mRNA interaction networks, such as the circHIPK3/miR-29b-c/COL1A2 network, are involved in GC development, progression, and reduced sensitivity to chemotherapy ( Pereira et al, 2020 ).…”
Section: The Effect Of Some Important Non-coding Rnas On Gastric Cancermentioning
confidence: 99%